Unit Blocks Play Activity; What Do You See From Their Play? (The Study of Mathematical Thinking Development Children 3 – 5 Years Old) - Eriva Syamsiatin (PG PAUD FIP UNIMED, 2017)
Unit block was one of famous children’s play materials. Children develop and practice variety of skills during play activities with blocks. Unit blocks help children to construct mathematical thinking skills and concept. The study was to reveal early mathematic thinking skills development children age 3-5 years old that showed during playing unit blocks. The unit blocks was used in this was Pratt’s Unit Blocks. Pratt’s block has a unique composition of block about 5 1/2